Setting up the first human milk bank in Uganda: a success story from Nsambya hospital - Nakibuuka, Victoria; Kainza, Janat; Nasiima, Ritah; Nalunga, Sanyu; Nazziwa, Ritah; Mponye, Hamim; Nuwahereza, Christinah; Kyambadde, Ronald; Nantenza, Racheal; Nassonko, Caroline; Nalubwama, Barbara; Nabwami, Immaculate; et al. (Frontiers in Nutrition, 2024)
Background: The World Health Organization (WHO) strongly recommends the use of donor human milk (DHM) for low-birth-weight infants when mother's own milk is unavailable. However, the use of DHM requires the availability of human milk banks (HMBs), the majority of which are in middle and high-income countries. This study describes the experience in setting up the HMB in Uganda at St. Francis Hospital Nsambya The establishment of the first HMB in Uganda followed a stepwise approach using the PATH's Resource Toolkit for Establishing and Integrating Human Milk Banks. The steps included: performing a facility readiness assessment, implementing quality control measures, forming and training a committee for the Baby Friendly Hospital Initiative, establishing a monitoring and evaluation system, developing a communication strategy, engaging with the Ministry of Health, providing staff training by a Human Milk Bank consultant, and maintaining regular coordination by a dedicated technical team. Results. A total of 170 donors have been screened and of these 140 have donated milk with a mean age of 26 years since November 2021. A total of 109 admitted neonates have received the milk; majority (88%) are preterm infants mean gestational age (34 weeks). A total of 90 liters have been collected and 76 distributed. The challenges included: lack of human milk banking guidelines, use of unpasteurized milk, lack of communication strategy, lack of clear model infrastructure and lactation training. We addressed the challenges: by drafting guidelines, training on human milk Banking and lactation,designed communication messages using videos and brochures, visited Pumwani hospital and remodeled the Human Milk Bank Assessing the experiences and attitudes of mothers, donors, healthcare providers, and hospital leaders revealed concerns about milk safety and fear about potential attachments or acquired traits through the donated milk to the babies that may receive it. Donors viewed milk donation as a life-saving act, although fears of breast cancer and lumps arose from misconceptions. To address these perspectives, creative media, such as videos and messages, were designed to raise awareness, promote behavioral change, and create demand for the HMB services. The establishment and integration of HMB services at hospitals in Uganda is feasible.